Faktor yang Mempengaruhi Emotional Exhaustion pada Perawat di Rumah Sakit: A Cross-Sectional Study - Ayatulloh, Daviq; Priyantini, Diah; Basri, Ahmad Hasan; Ahmadi, Ade Faiz (Universitas Muhammadiyah Surabaya, 2025)
Introduction: Emotional exhaustion among hospital nurses represents a major occupational health challenge, particularly in healthcare systems facing increasing service demands and workforce constraints. Identifying organizational determinants based on the Job Demands–Resources (JD-R) framework is essential to inform context-specific workforce strategies. Methods: A cross-sectional study was conducted among 72 nurses working in various clinical units at a hospital in Gresik, Indonesia. Cluster sampling was applied to ensure proportional representation across units. Emotional exhaustion was measured using the Emotional Exhaustion subscale of the Maslach Burnout Inventory–Human Services Survey. Job demands (workload, emotional demands, role conflict, workplace incivility) and job resources (supervisor support, organizational support, team support, job autonomy) were assessed using validated questionnaires. Data were analyzed using multiple linear regression to determine the relative contribution of each predictor. Results: Job demands and job resources were significant predictors of emotional exhaustion (p < 0.001), accounting for 50% of the variance. Workload emerged as the strongest positive predictor, followed by emotional demands. Among job resources, supervisor support demonstrated the most substantial protective effect. Higher job demands were associated with increased emotional exhaustion, whereas stronger job resources were associated with reduced levels of exhaustion. Discussion: The findings reinforce the JD-R framework, highlighting the interplay between structural workload pressures and organizational support mechanisms in shaping nurse wellbeing. Organizational strategies focusing on workload management and strengthening supervisory support may contribute to reducing emotional exhaustion in hospital settings.